Connectivity in the deep: Phylogeography of the velvet belly lanternshark. (September 2016) - Gubili, Chrysoula; Macleod, Kirsty; Perry, William; Hanel, Pia; Batzakas, Ioannis; Farrell, Edward D.; Lynghammar, Arve; Mancusi, Cecilia; Mariani, Stefano; Menezes, Gui M.; Neat, Francis; Scarcella, Giuseppe; et al.
Abstract: The velvet belly lanternshark, Etmopterus spinax, is a deep-sea bioluminescent squaloid shark, found predominantly in the Northeast Atlantic and Mediterranean Sea. It has been exposed to relatively high levels of mortality associated with by-catch in some regions. Its late maturity and low fecundity potentially renders it vulnerable to over-exploitation, although little remains known about processes of connectivity between key habitats/regions. This study utilised DNA sequencing of partial regions of the mitochondrial control region and nuclear ribosomal internal transcribed spacer 2 to investigate population structure and phylogeography of this species across the Northeast Atlantic and Mediterranean Basin. Despite the inclusion of samples from the range edges or remote locations, no evidence of significant population structure was detected. An important exception was identified using the control region sequence, with much greater (and statistically significant) levels of genetic differentiation between the Mediterranean and Atlantic. This suggests that the Strait of Gibraltar may represent an important bathymetric barrier, separating regions with very low levels of female dispersal. Bayesian estimation of divergence time also places the separation between the Mediterranean and Atlantic lineages within the last 100, 000 years, presumably connected with perturbations during the last Glacial Period. These results demonstrate population subdivision at a much smaller geographic distance than has generally been identified in previous work on deep-sea sharks. This highlights a very significant role for shallow bathymetry in promoting genetic differentiation in deepwater taxa. It acts as an important exception to a general paradigm of marine species being connected by high levels of gene-flow, representing single stocks over large scales. It may also have significant implications for the fisheries management of this species. Highlights: First analysis of connectivity in the velvet belly lanternshark, a vulnerable deep sea shark. Identification of a major oceanographic barrier to gene-flow. Important implications for biogeography, fisheries management & conservation.